Modelling and TITO predictive control of laboratory system - Honc, Daniel; Havlíček, Libor; Dušek, František (Univerzita Pardubice, 2008)
Laboratory pilot-plant is designed and realized as a system for process control education and research - e.g. mathematical modelling, experimental identification, controller design, real-time control. Key features of laboratory hydraulic-pneumatic system are described in the paper. Nonlinear mathematical-physical model of the process and its linearized state-space realization are briefly presented. TITO predictive controller is designed (from linearized model) as a control application example. Simulated and real control experiments are compared to verify the model quality. Nonlinear model contains emulation of typical process noises and disturbances and can be treated as an "image of real process" or benchmark test process.